2008
DOI: 10.1086/589672
|View full text |Cite
|
Sign up to set email alerts
|

Do Analyst Conflicts Matter? Evidence from Stock Recommendations

Abstract: We examine whether conflicts of interest with investment banking and brokerage businesses induce sell-side analysts to issue optimistic stock recommendations and, if so, whether investors are misled by such biases. Using quantitative measures of potential conflicts constructed from a novel data set containing revenue breakdowns of analyst employers, we find that recommendation levels are indeed positively related to conflict magnitudes. The optimistic bias stemming from investment banking conflicts was especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(101 citation statements)
references
References 52 publications
6
94
1
Order By: Relevance
“…On the other hand, another strand of literature finds quite the reverse concerning conflicts of interest and, thus, exculpates analysts. Iskoz (2003) and Agrawal and Chen (2008), for instance, provided evidence that affiliated analysts do not seem to issue more biased reports than analysts from independent research firms. Cowen, Groysberg, and Healy (2006) even found that analysts employed by banks which fund research through underwriting and trading activities issued less optimistic forecasts and recommendations as opposed to banks which do not perform M&A services at all.…”
Section: 2mentioning
confidence: 99%
“…On the other hand, another strand of literature finds quite the reverse concerning conflicts of interest and, thus, exculpates analysts. Iskoz (2003) and Agrawal and Chen (2008), for instance, provided evidence that affiliated analysts do not seem to issue more biased reports than analysts from independent research firms. Cowen, Groysberg, and Healy (2006) even found that analysts employed by banks which fund research through underwriting and trading activities issued less optimistic forecasts and recommendations as opposed to banks which do not perform M&A services at all.…”
Section: 2mentioning
confidence: 99%
“…Bradshaw et al (2003) find that analysts routinely manipulate their investment advice in response to investment banking pressure. A recent study by Agrawal and Chen (2008) documents that the level of recommendations is positively related to the conflicts of interest an analyst faces. However, they find that the market properly discounts the positive bias.…”
Section: Related Literaturementioning
confidence: 99%
“…There are a number of years for which we do not find any sample REIT IPO activity (i.e., 1982, 2000, 2001, and 2008. We also find that 26 of the sample REITs were listed prior to 1982.…”
Section: Sample Selection and Descriptive Statisticsmentioning
confidence: 60%
“…3 There is a large literature that investigates bias in analyst recommendations (i.e., Dugar and Nathan (1995), Lin and McNichols (1998), Michaely and Womack (1999), and, more recently, Iskoz (2003), Malmendier and Shanthikumar (2007), Agrawal and Chen (2008), and Kadan, Madureira, Wang, and Zach (2009)) have demonstrated that analyst bias is at least partly driven by underwriting relationships. 4 It is important to note that in this paper we are ambiguous on whether REITs under or over perform after IPOs and SEO.…”
mentioning
confidence: 99%